2020
DOI: 10.1136/bmjopen-2020-041295
|View full text |Cite
|
Sign up to set email alerts
|

Association between biomarkers and COVID-19 severity and mortality: a nationwide Danish cohort study

Abstract: ObjectiveTo evaluate the association between common biomarkers, death and intensive care unit (ICU) admission in patients with COVID-19.DesignRetrospective cohort study. From electronic national registry data, we used Cox analysis and bootstrapping to evaluate associations between baseline levels of biomarkers and standardised absolute risks of death/ICU admission, adjusted for age and gender.SettingAll hospitals in Denmark.Participants1310 patients aged ≥18 years admitted to hospital with COVID-19 from 27th o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 22 publications
4
61
1
1
Order By: Relevance
“…Several publications from China addressed the prognostic value of different parameters in predicting disease severity and short-term survival in COVID-19 patients [ 41 , 42 , 43 , 44 , 45 , 46 ]. Of note, although limited by a small size and the single center character, our data show significantly elevated bio-ADM levels in non-survivors compared to survivors with a moderate predictive value for 28-day mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Several publications from China addressed the prognostic value of different parameters in predicting disease severity and short-term survival in COVID-19 patients [ 41 , 42 , 43 , 44 , 45 , 46 ]. Of note, although limited by a small size and the single center character, our data show significantly elevated bio-ADM levels in non-survivors compared to survivors with a moderate predictive value for 28-day mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Procalcitonin was not routinely measured in the ICUs that participated in our study, although it could be a helpful tool in the decision regarding early use of antibiotics. However, procalcitonin levels are generally elevated in COVID-19 ICU inpatients [22], and data are needed to assess a possible specific threshold.…”
Section: Vap Risk Factors Analysismentioning
confidence: 99%
“…11,21,22 While previous studies have identified other laboratory values, such as red cell distribution width and D-dimer levels, as significant predictors, they did not contribute to this algorithm. 3,14 BUN was the only laboratory value in the algorithm and a missing value did not influence the score. This suggests that clinicians do not need to order or wait for other test results to estimate a patient’s probability of dying.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of predictors of dying from COVID-19 infection have had a small number of deaths; [1][2][3][4][5][6][7] used comorbid conditions, diagnoses ,and severity indices from electronic medical records that may not be known at the time of admission; 4,[8][9][10][11][12][13] or included specialized laboratory tests-such as levels of C-reactive protein, troponin, and D-dimers-that are not readily available for urgent triage of patients for hospital admission or intensive care. 14 Some studies were done in ethnically homogenous populations such as Wuhan, China 1 or Italy, 15 in specific populations such as nursing home residents, 16 or among patients already being treated in an intensive care unit (ICU) 6,9 Although some studies applied machine learning methods to develop predictive models, 1,5,17,18 none have been based on measurements available at the time of triage in a large diverse population, nor have they been translated into calculators that can be used in clinical settings.…”
mentioning
confidence: 99%